The Effectiveness of Learning Management Systems (LMS) in Enhancing Learning Experiences toward Achieving SDG 4: Quality Education - Rhezwan Dhaifullah Romdhoni; Ahmad Romdhoni (Journal of Information System and Education Development, 2026)
This study examines the effectiveness of the use of the Learning Management System (LMS) in improving the student learning experience in higher education, as well as its contribution to the achievement of the goals of Quality Education (SDG 4). Using the Systematic Literature Review (SLR) method, this study analyzed 15 scientific articles published between 2020 and 2025, which focused on the use of LMS in improving student learning outcomes, motivation, and independence. The results showed that the use of LMS consistently improved learning outcomes by between 10% to 20%, as well as increased student learning independence by between 15% to 17%. LMSs such as Moodle, Edmodo, and Google Classroom have proven to be effective in supporting flexible and interactive learning. In addition, the integration of artificial intelligence in the LMS further strengthens the adaptive learning personalization. The study also found that LMS plays an important role in supporting the achievement of SDG 4 by expanding access to inclusive and sustainable quality education, as well as improving the effectiveness, efficiency, and quality of learning around t he world, thereby supporting broader education transformation